Genetic/Environmental Influences in Fragile X Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
The genetic and environmental factors influencing cognitive outcomes in 120 children (80 boys and 40 girls) with the fragile X full mutation and their unaffected siblings were determined by in-home evaluations and reported from the Departments of Psychiatry and Pediatrics, Stanford University, CA.